Cannabidiol Administered During Peri-Adolescence Prevents Behavioral Abnormalities in an Animal Model of Schizophrenia - Peres, Fernanda F.; Diana, Mariana C.; Levin, Raquel; Suiama, Mayra A.; Almeida, Valéria; Vendramini, Ana M.; Santos, Camila M.; Zuardi, Antônio W.; Hallak, Jaime E. C.; Crippa, José A.; Abílio, Vanessa C. (Frontiers in Pharmacology, 2018)
Schizophrenia is considered a debilitating neurodevelopmental psychiatric disorder and its pharmacotherapy remains problematic without recent major advances. The development of interventions able to prevent the emergence of schizophrenia would therefore represent an enormous progress. Here, we investigated whether treatment with cannabidiol (CBD – a compound of Cannabis sativa that presents an antipsychotic profile in animals and humans) during peri-adolescence would prevent schizophrenia-like behavioral abnormalities in an animal model of schizophrenia: the Spontaneously Hypertensive Rat (SHR) strain. Wistar rats and SHRs were treated with vehicle or CBD from 30 to 60 post-natal days. In experiment 1, schizophrenia-like behaviors (locomotor activity, social interaction, prepulse inhibition of startle and contextual fear conditioning) were assessed on post-natal day 90. Side effects commonly associated with antipsychotic treatment were also evaluated: body weight gain and catalepsy throughout the treatment, and oral dyskinesia 48 hours after treatment interruption and on post-natal day 90. In experiment 2, serum levels of triglycerides and glycemia were assessed on post-natal day 61. In experiment 3, levels of BDNF, monoamines, and their metabolites were evaluated on post-natal days 61 and 90 in the prefrontal cortex and striatum. Treatment with CBD prevented the emergence of SHRs’ hyperlocomotor activity (a model for the positive symptoms of schizophrenia) and deficits in prepulse inhibition of startle and contextual fear conditioning (cognitive impairments). CBD did not induce any of the potential motor or metabolic side effects evaluated. Treatment with CBD increased the prefrontal cortex 5-HIAA/serotonin ratio and the levels of 5-HIAA on post-natal days 61 and 90, respectively. Our data provide pre-clinical evidence for a safe and beneficial effect of peripubertal and treatment with CBD on preventing positive and cognitive symptoms of schizophrenia, and suggest the involvement of the serotoninergic system on this effect.